Extraction of Moving Objects on Underwater Video Using Method of Subtraction the Background Modeling Results - Setyawan, FX Arinto; Sulistiyanti, Sri Ratna (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2017)
Abstract—This paper proposes a method for extracting moving objects on an underwater surveillance video. Video obtained using an underwater camera to capture the environmental conditions of the area. This research is the initial stage of the underwater surveillance system. Underwater surveillance system enables objects passing can be recognized shapes, types, and its behavior. The extraction method used in this research is a subtraction between the current frames with the background modeling results. Underwater video retrieval has a high level of difficulty because the background is always changing either due to a change the intensity and the movement of water currents. Therefore, it needs to be made an appropriate background model to address this problem. Modeling of the background on this research using adaptive modeling method, where the intensity of the background pixels is updated based on inference of the background intensity before. If the intensity of the pixels changed drastically beyond the allowed threshold value, the pixel is considered as the pixels of the object and the pixel values of the background model are updated based on this pixel value. The effectiveness of the proposed method is expressed with the value of recall and precision. The average recall value of the three videos is 62% and the value of its precision is 82%.Keywords— Extraction Object, Background Modeling, Adaptive Modeling, underwater surveillance.